Developing new food products for changing marketplace - Brody, Aaron L (CRC Press, 2008)
When Brody and Lord could find no suitable textbook for their course in product policy for food marketing majors at St. John's University, they cobbled together notes and invited in speakers for several years. Finally they had had enough, and invited specialists to write accounts of the various aspects. They emphasize that developing new food products is a systemic process that must engage every part of the company, including marketing, design, the laboratory, legal, and of course the bookkeeper. Well, the big boss can probably stay in the Bahamas, in fact it is probably better that way.